2010
DOI: 10.1007/s10265-010-0342-5
|View full text |Cite
|
Sign up to set email alerts
|

Two CLE genes are induced by phosphate in roots of Lotus japonicus

Abstract: Genes of CLE (CLAVATA3/ESR-related) family encode peptide ligands that regulate plant development in response to external stimuli such as rhizobial infection and the nitrate application as well as various internal stimuli. To investigate whether LjCLE gene(s) may involve in plant response to inorganic phosphate (Pi), we analyzed Pi responses of 39 LjCLE genes in hydroponically grown Lotus japonicus plants (ecotype Miyakojima 'MG-20'). Two LjCLE genes, LjCLE19 and 20, were up-regulated specifically and greatly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 35 publications
(45 reference statements)
0
33
0
Order By: Relevance
“…Indeed, recent expression studies indicated that LjCLE-RS2 in L. japonicus roots is induced by KNO 3 , whereas expression levels of LjCLE19/ LjCLE20 were stimulated when plants were grown at high phosphate concentrations. 18,69 It is tempting to speculate that autoregulation LRR receptor kinases expressed in roots are receptors for CLE peptides induced by high nitrate or phosphate levels.…”
Section: Shoot-controlled Autoregulation Of Mycorrhization In Legumesmentioning
confidence: 99%
“…Indeed, recent expression studies indicated that LjCLE-RS2 in L. japonicus roots is induced by KNO 3 , whereas expression levels of LjCLE19/ LjCLE20 were stimulated when plants were grown at high phosphate concentrations. 18,69 It is tempting to speculate that autoregulation LRR receptor kinases expressed in roots are receptors for CLE peptides induced by high nitrate or phosphate levels.…”
Section: Shoot-controlled Autoregulation Of Mycorrhization In Legumesmentioning
confidence: 99%
“…Growing evidence indicates that SSPs play a critical role in legume growth, development, and productivity, particularly in relation to nutrient acquisition and use (Funayama-Noguchi et al, 2011;Imin et al, 2013;Okamoto et al, 2013;MohdRadzman et al, 2015MohdRadzman et al, , 2016Wang et al, 2015). The CLAVATA3/EMBRYO-SURROUNDING REGION (CLE) peptides are particularly well studied in legumes due to their role in the systemic negative feedback mechanism known as autoregulation of nodulation (Mortier et al, 2010;Okamoto et al, 2013;Kassaw et al, 2017) and in local regulation by nitrate-induced CLEs (Hastwell et al, 2015).…”
mentioning
confidence: 99%
“…The CLAVATA3/EMBRYO-SURROUNDING REGION (CLE) peptides are particularly well studied in legumes due to their role in the systemic negative feedback mechanism known as autoregulation of nodulation (Mortier et al, 2010;Okamoto et al, 2013;Kassaw et al, 2017) and in local regulation by nitrate-induced CLEs (Hastwell et al, 2015). Phosphate-induced CLEs also have been reported in Lotus japonicus (Funayama-Noguchi et al, 2011;Handa et al, 2015), while other legume CLEs are involved in root apical meristem maintenance (Oelkers et al, 2008). A member of the C-TERMINALLY-ENCODED PEPTIDE (CEP) family in M. truncatula, MtCEP1, inhibits lateral root growth and promotes nodulation via signaling pathways dependent on the Leu-rich repeat receptor-like kinase MtCRA2 (Imin et al, 2013;Huault et al, 2014;Mohd-Radzman et al, 2016).…”
mentioning
confidence: 99%
“…7 this contrasts with the major role for strigolactones in phosphate control of shoot branching of rice and Arabidopsis 8,9 and indicates that the integration of strigolactones into our understanding of nutrient response will be complex. new data presented here, along with the recent discovery of phosphate specific CLE peptides, 10 indicates a potential role for PsnarK, a component of the autoregulation of nodulation pathway, in phosphate control of nodulation.…”
mentioning
confidence: 58%
“…In contrast, Psnark mutants exhibited a clear supernodulating phenotype under both phosphate treatments, with no significant reduction in nodule number in response to phosphate limitation. With the recent description of phosphate-induced CLE peptides, 10 the potential for integration of phosphate to enhance nodulation, as strigolactone-deficient mutants form significantly fewer nodules and this can be restored by synthetic strigolactones. 5,18 Strigolactones appear to influence nodule development after root hair curling but before visible nodule emergence (Fig.…”
Section: The Role Of Strigolactones In the Response To Phosphorus Andmentioning
confidence: 99%